Starfall: a heavy rain of stars in 'turning on' AGN. Issue 3 (17th May 2022) - McKernan, B; Ford, K E S; Cantiello, M; Graham, M; Jermyn, A S; Leigh, N W C; Ryu, T; Stern, D
ABSTRACT: As active galactic nuclei (AGN) 'turn on', some stars end up embedded in accretion discs around supermassive black holes (SMBHs) on retrograde orbits. Such stars experience strong headwinds, aerodynamic drag, ablation, and orbital evolution on short time-scales. The loss of orbital angular momentum in the first ∼0.1 Myr of an AGN leads to a heavy rain of stars ('starfall') into the inner disc and on to the SMBH. A large AGN loss cone ( θ AGN, lc ) can result from binary scatterings in the inner disc and yield tidal disruption events (TDEs). Signatures of starfall include optical/UV flares that rise in luminosity over time, particularly in the inner disc. If the SMBH mass is $M_{\rm SMBH} \gtrsim 10^{8}\, M_{\odot }$, flares truncate abruptly and the star is swallowed. If $M_{\rm SMBH}\lt 10^{8}\, M_{\odot }$, and if the infalling orbit lies within θ AGN, lc, the flare is followed by a TDE that can be prograde or retrograde relative to the AGN inner disc. Retrograde AGN TDEs are overluminous and short-lived as in-plane ejecta collide with the inner disc and a lower AGN state follows. Prograde AGN TDEs add angular momentum to inner disc gas and so start off looking like regular TDEs but are followed by an AGN high state. Searches for such flare signatures test models of AGN 'turn on', SMBH mass, as well as disc properties and the embedded population.